Enantioselective Synthesis of Axially Chiral Benzimidazoles Bearing a C–N axis via Pd-Catalyzed Buchwald–Hartwig Amination - Zhang, Peng; Feng, Jia; Liu, Ren-rong (Synlett, 2022)
Benzimidazole atropisomers bearing a C–N axis are privileged structural frameworks in pharmaceutical and natural products, thus appealing an increasing interest for its asymmetric synthesis. Here, we briefly discuss recent advances in the asymmetric synthesis of benzimidazole atropisomers with a C–N axis, with particular attention to our recently developed palladium-catalyzed intramolecular Buchwald–Hartwig amination strategy.
Keywords: atropisomerism; palladium; amination; benzimidazole atropisomers; asymmetric catalysis